KONSEP DASAR KONSELING PENDIDIKAN ISLAM - Mufti, Zaki Aulia; Ulfatmi, Ulfatmi; Afnibar, Afnibar; Kenedi, Gusril (Studi Multidisipliner: Jurnal Kajian Keislaman, 2024)
Humans are inseparable from various life problems that require solutions both individually and with the help of others. In this context, Islamic educational counseling plays an important role in providing assistance both academically and spiritually. This article aims to examine in depth the various concepts, vision and mission, goals and paradigms of Islamic educational counseling. This article uses a qualitative approach with a library research design. The results in this article indicate that Islamic educational counseling is a guidance process that aims to help individuals achieve balanced development mentally, emotionally, and spiritually. The basis for the development of Islamic educational counseling is based on the Qur'an, hadith, and kauniyah verses. The vision and mission of Islamic education counseling emphasizes the formation of individuals who are pious, noble, and able to face the challenges of life with guidance in accordance with Islamic teachings. The objectives of Islamic education counseling include the development of morals and spirituality, problem solving, improving the quality of life, and building character and leadership. Furthermore, the paradigm of Islamic educational counseling, with a holistic approach, integration of Islamic principles, and family and community involvement, describes a way of counseling that focuses on individual balance and empowerment.